A modified tracking algorithm for maximum power tracking of solar array - Hua, Chihchiang; Lin, Jongrong (Energy conversion and management, 2004)
Maximum power point tracking (MPPT) techniques are usually used for solar power applications. This paper discusses: (1) various connection methods between solar arrays and loads and (2) various maximum power point control methods and MPPT algorithms. In this paper, the solar array is treated as a current source instead of a voltage source. Analytical models are built for the solar array and converter on the basis of the data sheet of the manufacturer and the principle of energy conservation. An improved MPPT algorithm was proposed to reduce the power loss in the tracking process. A digital signal processor (DSP) based controller was constructed to implement the proposed MPPT control, and the experimental results are presented.